2020
DOI: 10.1186/s41983-020-0150-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in patients with chronic tension-type headache and its relation to neuroendocrine hormones

Abstract: Background: Tension-type headache is the most common headache to be seen in clinical practice. Depression is highly prevalent in chronic tension-type headache (CTTH) patients attending the clinical settings. Cognitive impairment and neuroendocrine dysregulation had been reported in patients with depression and patients with CTTH. Objective: To assess the cognitive performance and investigate its possible relations to neuroendocrine levels in patients with CTTH. Subjects and methods: Patients with CTTH, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…From the 15,316 records identified by the search methods, 37 studies (Demirci and Savas, 2002 ; Weiner et al, 2006 ; Meeks et al, 2008 ; Shega et al, 2010 , 2012 ; Jonsson et al, 2011 ; Walteros et al, 2011 ; Ko et al, 2013 ; Pirrotta et al, 2013 ; Butterworth et al, 2014 ; Docking et al, 2014 ; Hagen et al, 2014 ; Martinsen et al, 2014 ; Pickering et al, 2014 ; Coppieters et al, 2015 ; Meeus et al, 2015 ; Öncü et al, 2015 ; Dos Santos Ferreira et al, 2016 ; Fernández-Lao et al, 2016 ; Santangelo et al, 2016 ; Schepker et al, 2016 ; Kaiho et al, 2017 ; Tzeng et al, 2017 ; Whitlock et al, 2017 ; Jordan et al, 2018 ; Ojeda et al, 2018 ; Pidal-Miranda et al, 2018 ; Qu et al, 2018 ; Van Der Leeuw et al, 2018b , 2020 ; Veronese et al, 2018 ; Gu et al, 2019 ; Ikram et al, 2019 ; Samartin-Veiga et al, 2019 ; Kotb et al, 2020 ; Latysheva et al, 2020 ; Nakai et al, 2020 ) were identified, a total of 52,373 patients with CP and 80,434 healthy control participants. These 37 studies included different types of CP: headache ( n = 7); fibromyalgia syndrome (FM) ( n = 6); low back pain ( n = 3); whiplash-associated disorder ( n = 2); foot pain ( n = 2); cancer pain ( n = 1); low back pain and knee pain ( n = 1); neuropathic pain ( n = 1); musculoskeletal pain, neuropathic pain, and FM ( n = 1); post-herpetic neuralgia ( n = 1); non-cancer pain ( n = 1); and other unclassified CP ( n = 13).…”
Section: Resultsmentioning
confidence: 99%
“…From the 15,316 records identified by the search methods, 37 studies (Demirci and Savas, 2002 ; Weiner et al, 2006 ; Meeks et al, 2008 ; Shega et al, 2010 , 2012 ; Jonsson et al, 2011 ; Walteros et al, 2011 ; Ko et al, 2013 ; Pirrotta et al, 2013 ; Butterworth et al, 2014 ; Docking et al, 2014 ; Hagen et al, 2014 ; Martinsen et al, 2014 ; Pickering et al, 2014 ; Coppieters et al, 2015 ; Meeus et al, 2015 ; Öncü et al, 2015 ; Dos Santos Ferreira et al, 2016 ; Fernández-Lao et al, 2016 ; Santangelo et al, 2016 ; Schepker et al, 2016 ; Kaiho et al, 2017 ; Tzeng et al, 2017 ; Whitlock et al, 2017 ; Jordan et al, 2018 ; Ojeda et al, 2018 ; Pidal-Miranda et al, 2018 ; Qu et al, 2018 ; Van Der Leeuw et al, 2018b , 2020 ; Veronese et al, 2018 ; Gu et al, 2019 ; Ikram et al, 2019 ; Samartin-Veiga et al, 2019 ; Kotb et al, 2020 ; Latysheva et al, 2020 ; Nakai et al, 2020 ) were identified, a total of 52,373 patients with CP and 80,434 healthy control participants. These 37 studies included different types of CP: headache ( n = 7); fibromyalgia syndrome (FM) ( n = 6); low back pain ( n = 3); whiplash-associated disorder ( n = 2); foot pain ( n = 2); cancer pain ( n = 1); low back pain and knee pain ( n = 1); neuropathic pain ( n = 1); musculoskeletal pain, neuropathic pain, and FM ( n = 1); post-herpetic neuralgia ( n = 1); non-cancer pain ( n = 1); and other unclassified CP ( n = 13).…”
Section: Resultsmentioning
confidence: 99%